Reviewing the literature on multiple themes of Islamic attire usage among Muslim women - Hasmad, Nurjannah; AlOsman, Abdulrahman (USIM Press, 2021)
Islam calls upon its men and women believer to preserve their chastity, in which one of the ways to achieve itis through proper clothing that covers their aurah. Various Quranic verses and prophetic traditions provide guidelines abouthow one should cover their aurah.Nevertheless, Islam does not specify thetype of clothing to be worn, affirming that that any clothes are permissible, as long as it followsthe guidelines of aurah covering. Even though it is undisputable that it is a religious commandment in Islam for itsbeliever to dress in a manner that their aurah is not revealed, the fact is that nowadays, many other themes other than religion are layering Islamic attire usageamongMuslim women whether it is hijab, jibab, abaya, orany other Islamic apparel.This article aims to review literatures related to the usageof Islamic attire among Muslim women within the last 10 years, focusing on the themes accompanying itamong Muslim women around the world. Adopting the library research method, official-based and academic-content literatures related to Muslim women attire from 2010 until 2020 are selected and analysed to discover the themes involved in the usageof Islamic attireamongMuslim women.This article found several important themes behind the usageof Islamic attireamong Muslim women,namely religion, culture, society, family, fashion,and media.The finding in this article may be useful for academics and researchers to further undertake the topic of Muslim women attire, as well as to fill the gaps on aspects yet to be studied on the topic of Muslim women attire.